A new model of acid fracturing based on boundary element method coupled with multi-field multi-phase process. (June 2020) - He, Yuting; Yang, Zhaozhong; Li, Xiaogang; Song, Rui
Highlights: A new acid fracturing model has been established. Thermal-hydro-mechanical-chemistry process has been considered. Carbon dioxide generated by acid rock reaction were considered. The factors affecting the acid fracturing have been analyzed. Abstract: In this research, the thermal-hydro-mechanical-chemistry coupling process involved in acid fracturing is simulated using 2D displacement discontinuity method combined with the finite volume method. Temperature field models, acid flow models, and acid rock reaction models are also established based on material conservation and energy conservation criteria. And the new acid fracturing method is used to solve the problem of rock deformation, fluid interference, fracture opening, temperature, acid rock reaction, multiphase flow, and carbon dioxide characteristics coupling. Simulations of larger scale acid fracturing are carried out to analyze the influence of injection rate, initial acid concentration, acid viscosity and initial reservoir temperature, and acid temperature on the bottom of the well on optimizing acidizing design. The results show: the acid rock reaction and its reaction product have a significant influence on the fracture extension. And the coupled process and the influence of carbon dioxide are necessary to be considered when studying the acid fracturing process. For obtaining as long as possible effective penetration distance of the acid, a larger injection rate can be selected, a larger initials acid concentration, a lower acid viscosity and a lower acid temperature at the bottom of the well.